Representasi Konten Humor dalam Iklan Televisi Shampo Head & Shoulders - Putra Akbar Pradina; Raditya Pratama Putra (UNISBA Press, 2023)
Abstract. Humor is an attitude that tends to be done to evoke joy and trigger laughter. We can find humor on any platform, for example on television shows and advertisements. There are lots of advertisements that use elements of humor in it to attract people's attention. Indirectly advertisements that use elements of humor to make people who watch are interested. In this study the method used was qualitative method using interview techniques and direct field observation in order to obtain the necessary data with the Ferdinand De Saussure Semiotic Analysis approach in perfecting this research report. This study aims to determine the meaning of Significe (marker) contained in head & shoulder shampoo advertisements. This is to find out the meaning of Signified (signified) and the advertising ethics contained in Head & Shoulder shampoo advertisements. There are as many as 29 million viewers who watch YouTube Head & Shoulders ads. Therefore, researchers are very interested in finding more in-depth information about Joe Taslim Head & Shoulders humorous Youtube advertisements. Based on the formulation of the problem and the results of the research, it can be concluded that there are signifiers, signifiers, and humor ethics in the research entitled